Design and Application Research of an Adaptive Obstacle Climbing Mechanism for Floor Sweeping Robot - Feng Shupeng; Wang Mingdi (Jixie chuandong)
Taking sweeping robot as the research object,solving the requirement of climbing higher steps and automatically adapting to different step heights in the process of robot running. An adaptive auxiliary obstacle climbing mechanism is designed,which is connected with the main driving wheel of the machine and is triggered by connecting rod mechanism when the step is touched to increase the additional driving force. The whole process of obstacle crossing is modeled by Euler dynamic equation. Combined with the application of the product in the actual family environment,the formula for calculating the torque of the key design parameters is given after excluding the distracters. Finally,the practical data of the mainstream products in the market are calculated,and the feasibility and application value of the auxiliary mechanism on the specific products are verified.